The efficiency of drawing high-strength wire with a high proportion of compressive stresses in the deformation scheme - V. P. Fetisov (Литьë и металлургия)
Drawing region ultralarge total of reductions with the prevailing influence of compressive stress provides relaxation local peak stresses and increase of the stock of plasticity ultraviolence brass plated wire for steel cord.